Proposal for the definition of Archival Science from a bibliographic and contextual analysis - Jaramillo, Orlanda; Betancur, María Cristina (Revista General de Información y Documentación, 2021)
This paper presents the research process that led to the presentation of an archival concept that addresses the current contexts permeated by information and communication technologies, documentary production in different media and the recognition of various records producers: archival science as a scientific discipline is part of the information sciences. It deals with the interactions between records, archives, production contexts and users through the use of techniques, principles and methods specific to records management, in order to guarantee rights, governance and transparency, as well as the identity and memory of Society.
Keywords: Archival science; Archival studies; Archival theory; Archival concept; Disciplinary basis